Human NK Cells: From Surface Receptors to the Therapy of Leukemias and Solid Tumors - MORETTA, LORENZO; Pietra, Gabriella; Montaldo, Elisa; Vacca, Paola; Pende, Daniela; Falco, Michela; Del Zotto, Genny; Locatelli, Franco; Moretta, Alessandro; Mingari, Maria Cristina (Frontiers in Immunology, 2014)
Natural Killer (NK) cells are major effector cells of the innate immunity. The discovery, over two decades ago, of MHC-class I specific NK receptors and subsequently of activating receptors, recognizing ligands expressed by tumor or virus-infected cells, paved the way to our understanding of the mechanisms of selective recognition and killing of tumor cells. Although NK cells can efficiently kill tumor cells of different histotypes in vitro, their activity may be limited in vivo by their inefficient trafficking to tumor lesions and by the inhibition of their function induced by tumor cells themselves and by the tumor microenvironment. On the other hand, the important role of NK cells has been clearly demonstrated in the therapy of high risk leukemias in the haploidentical hematopoietic cell (HSC) transplantation setting. NK cells derived from donor HSC kill leukemic cells residual after the conditioning regimen, thus preventing leukemia relapses. In addition, they also kill residual dendritic cells and T lymphocytes, thus preventing both GvHD and graft rejection.